The expression of prostaglandin receptors EP3 and EP4 in human cervix in post‐term pregnancy differs between failed and successful labor induction. (18th December 2013) - Roos, Nathalie; Blesson, Chellakkan S.; Stephansson, Olof; Masironi, Britt; Vladic Stjernholm, Ylva; Ekman‐Ordeberg, Gunvor; Sahlin, Lena
Abstract Objective To investigate expression and localization of prostaglandin receptors EP1‐4 and FP and localization of stromal factors CTGF (connective tissue growth factor), furin, calgranulin B and ALOX15 (arachidonate 15‐lipooxygenase) in human cervical tissue from post‐term women with failed or successful labor induction after prostaglandin priming. Design Experimental prospective clinical study. Setting Tertiary obstetric care center. Population Twenty‐six women giving birth post‐term, with failed or successful labor induction, and a control group consisting of 19 women with spontaneous onset of labor and delivery at term. Methods Biopsies were obtained from post‐term women with successful (responders; R) and failed (non‐responders; NR) labor induction. Women with spontaneous delivery at term were included as controls (C). mRNA expression was determined with real time PCR, protein expression and localization with immunohistochemistry. Main outcome measures Comparisons of mRNA and protein expressions between post‐term pregnancies with failed and successful labor induction as well as term controls. Results EP4 mRNA expression was down‐regulated concomitant with an up‐regulation of EP3 mRNA expression in cervix from the NR group as compared with the R group. In stroma, immunoreactivity of the EP4 protein was increased in the NR group as compared with R and C groups. Conclusions Failure of cervical ripening, after local application of prostaglandins for labor induction, may be caused by the increased expression of EP3 and concomitant decrease in EP4 expression.